Docência na socioeducação: desafios e possibilidades na atuação junto a adolescentes privados de liberdade - Carvalho, Juliana Maria de Almeida (Universidade Federal de São Carlos, 2021)
This study aimed to investigate the understanding of teachers about their role in socio-education, specifically at Fundação CASA. As specific objectives, the following were defined: to know the challenges, possibilities, and needs of teachers to work in socio-education, as well as to understand the perceptions of teachers about the contribution of education in this context to the rehabilitation of adolescents. With this in mind, semi-structured interviews were carried out with seven professors who work at an institution in the interior of São Paulo. The research was based on the Historical-cultural Theory, which is based on historical-dialectical Materialism. The results obtained indicate that the interviewees' reports pointed to different conceptions of socio-education, approaching from law enforcement to its political and social dimension. The peculiarities of the teacher's work in Adolescent Detention Centers were related to the difficulties encountered and included the very condition of students' deprivation of freedom, the existence of learning gaps, issues related to the devaluation of the teaching work, and, mainly, the procedures institutions that generate tension between faculty and staff. As potentials and possibilities of educational work, the construction of identity and strengthening of teacher self-esteem and the significant learning of inpatients were highlighted. Other aspects mentioned referred to changes in teacher practice with the onset of the pandemic, as well as the need for specific continuing education to work in the area. It is argued that the teaching performance in socio-education is marked by several challenges, among which the precariousness of the teacher's work evidenced by the type of employment relationship of these professionals with the Department of Education, which has historical origins, but which is not restricted to this professional field.
Teaching in socio-education: challenges and possibilities in working with adolescents deprived of freedom
Keywords: Socioeducação; Trabalho docente; Adolescentes privados de liberdade; Socioeducation; Teaching work; Teenagers deprived of liberty; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM